Pengaruh Kinerja Keuangan dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Pengungkapan Corporate Sosial Responsibility sebagai Variabel Moderasi - Aprillia Anggraeni; Wulandari Agustiningsih (CV. Ulil Albab Corp, 2023)
The purpose of this study is to determine the determinants of financial performance and firm size on company value in the banking sector listed on the Indonesia Stock Exchange in 2019-2021 using the purposive sampling test method, with CSR disclosure as the moderator variable. There are 20 companies in the banking industry that meet the criteria with a sample size of 60. This study utilizes multiple linear analysis methods with secondary data types. The results of this study indicate that the relationship between financial performance and firm size has a simultaneous effect on company value. Financial perfiormance has no significant impact on company value,firm size has significant positif mpact on company value. CSR cannot strengthen the relationship between financial performance and company value, while CSR cannot strengthen the relationship between firm size and company value. This is because the large size of the company, the more people will pay attentionn to the social programs implemented so that the greater the CSR is carried out.